Nursing Solved Question Papers for General Nursing and Midwifery IIIrd Year - Bhardwaj Naina; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2012)
The book is written with great attention and concentration keeping in mind the basic requirement of IIIrd year nursing students. It contains solved question paper pediatric nursing, midwifery and gynecology and community health nursing with detailed explanation and important theory given at the beginning of every subject and to point explanatory answers of the questions in the simple language. It is ready reference tool from the examination point of view. This book helps the students prepare for the examination in an easy and meaningful way.
Keywords: General Nursing and Midwifery,MCQs and Self-assessment; Electronic books